Targeting signaling pathways in multiple myeloma: Pathogenesis and implication for treatments - Hu, Jingping; Hu, Wei-Xin (Cancer letters, 2018)
Multiple myeloma (MM), which is characterized by osteolytic bone lesions, anemia, hypercalcemia, and renal failure, accounts for approximately 10% of all hematologic malignancies. Although the therapeutic landscape of MM has evolved spectacularly over the past decades with 5-year median survival over 50%, most of these patients relapse eventually. The widely recognized therapeutic approaches include chemotherapy, radiation, stem cell transplant, and monoclonal antibody therapy. Former studies have implied that the proliferation, survival, migration and drug resistance of MM cells are in association with the activation of several signaling pathways. In this review, we intended to focus on the major signaling pathways such as PI3K/Akt/mTOR, Ras/Raf/MEK/MAPK, JAK/STAT, NF-κB, Wnt/β-catenin, and RANK/RANKL/OPG, that contribute to the pathogenesis of the MM and the therapeutic approaches developed to target them. •Summarized the most important signaling pathways that participated in the pathogenesis of multiple myeloma.•Summarized the evaluation methods and therapeutic strategies developed for these signaling pathways.•Implications for future directions with these signaling pathways.